Sistem Chaos Model Risiko Keuangan: Analisis Dinamik - Siti Hadiaty Yuningsih; Sukono Sukono; Endang Rusyaman (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
Chaos phenomena appear in dynamic, nonlinear and deterministic systems. One model that is being intensively researched is financial risk. This model has system variables such as interest rate, investment demand, and stock price index. This study shows that the new financial system has interesting characteristics including multistability equilibrium points, Lyapunov exponents and bifurcation diagrams. The results of this study use MATLAB for phase diagrams of the financial system. The Lyapunov exponent and analysis of the Bifurcation diagram have been generated showing the chaotic phenomena in the intervals 0 a 15 and 0 b 0.25. The resulting Kaplan-Yorke dimension is 2.2506. The results of this study can be used to predict financial risk chaos.